Preventing Occupational Noise-Induced Hearing Loss: A Systematic Review of Effective Interventions and Best Practices - Clarke, Alessandra; Zaidi, Moazzam; Kitila, Aiggan (New Zealand Journal of Health and Safety Practice, 2025)
Introduction: Noise is a common workplace hazard that can seriously affect worker health, including causing occupational noise-induced hearing loss (ONIHL). Under the Health and Safety at Work Act 2015, workplaces in New Zealand must take all reasonably practicable steps to manage this risk. This systematic review aims to identify evidence-based interventions to prevent occupational-induced hearing loss, with a focus on guiding workplaces in adopting the most effective measures. Methods: A systematic review was conducted to synthesise evidence from studies published between 2000 and 2024. Relevant literature was identified through a PubMed/MEDLINE database search using a combination of keywords and terms related to occupational noise, hearing loss, interventions, and best practices. Results: The review identified several effective strategies to minimise the risk of occupational noise-induced hearing loss, including purchasing quieter machinery, insulating noisy equipment, and improving workplace practices such as regular hearing tests, employee training, and awareness programmes. Additionally, the use of hearing protection devices was recommended to address residual noise exposure. Keywords: Occupational noise; Hearing loss; Best practices; Intervention; Systematic review